A construção da memória do desenvolvimento socioeconômico nas revistas Carta Capital e Veja: uma análise de conteúdo das revistas Carta Capital e Veja - Jacobini, Maria Lucia de Paiva (2009)
This paper intends to analyze how the memory about socioeconomic development is formed by Carta Capital and Veja magazines. From a explanation on the crisis of the modern science paradigm and the understanding of Latin America as a possible alternative, the objective is to discuss whether the content presented by each magazine is connected to the idea of socioeconomic development and the peculiarities of the Brazilian context and, from this, question the approach of themes specially related to already developed countries, such as consumption, economic growth and industrial modernization and technology. In order to achieve such objective and deepen the economical aspect, it is used the concept of socioeconomics as understood by Celso Furtado, accompanied by authors such as Boaventura Sousa Santos, Martín-Barbero and Edgard Morin that think about the relationship between communication and culture in Latin America and the conception of miscegenation as an alternative to the uniformity exported by developed countries. Culture Semiotics and the ideas of Iuri Lotman about how memory is formed and how it helps to understand the composition of news and its relation to the context in which it is inserted. Through this theoretical basis, both magazines are analyzed in a two-year period, between 1996 and 1998, focusing on the construction of national memory about socioeconomic development. The need to reflect about the construction of memory is important in order to understand and criticize Brazilian reality and is a step in the quest for national socioeconomic development, independent of important standards and more consistent with the internal situation and its specific features, not covered by certain exogenous ideas that are disseminated by Veja, in contrast to the critical postures of Carta Capital